Perceptions and Practices of Nepalese Mothers in Child Discipline and Learning - Sharma, Prakash; Adhikari, Bishnu Kumar; Thapa, Pramila; Rijal, Alisha (Butwal Campus Journal, 2025)
Punishment practices play a central role in shaping children’s early social, emotional, and behavioral development because, it is estimated that around two-thirds of children are regularly subjected to violent punishment at home, with approximately 1.2 billion experiencing corporal punishment globally. The purpose of this study is to explore mothers’ perception and practices regarding the impact of punishment and reward to change the behaviors of children, and to assess the alternative strategies of punishment in discipline and learning for children. This study employed the narrative inquiry research design under the qualitative method, thirteen mothers of children attending community managed Early Childhood Development (ECD) centers were purposively selected until data saturation. Open-ended interviews were conducted at participants’ homes and ECD centers. Audio-recorded, transcribed verbatim, and analyzed thematically. Trustworthiness was ensured through member checking, cross-checking of coding, audit trails, and reflexivity. The study discovered that mothers in the study area used punishment to control destructive activities and trigger learning, which had negative impacts, while mild or conscious punishment strategies had positive impacts on children’s discipline and learning. Cell phones, chocolate, toys, love and affection can be the alternative strategies of punishment to replace traditional concept of punishment. It is concluded that, while teaching and disciplining children, traditional forms of punishment can be replaced with toys, chocolate, cell phones, love and affection as an alternative strategy of punishment.